REVIVING VERNACULAR ARCHITECTURE: SUSTAINABLE STRATEGIES FROM TRADITIONAL BUILDING PRACTICES - Hamidova Mohigul Hayotovna; Vohidov Shakhzod Kenjayevich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: Vernacular architecture, shaped by climate, culture, and locally available materials, offers time-tested solutions for sustainable living. This article investigates how traditional architectural techniques can inform modern eco-friendly design, particularly in arid and semi-arid regions like Central Asia. By analyzing examples from Uzbekistan, India, and North Africa, the study highlights how passive cooling, natural materials, and spatial organization can reduce environmental footprints. The paper argues for integrating vernacular wisdom with modern technology to create architecture that is both culturally rooted and ecologically responsible.